Social Media Marketing Activities to Drive Purchase Intention in Local Skincare: A Study of Consumer Engagement Mediation - Nyka Fahma Utami; Yolanda Masnita; Kurniawati Kurniawati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Inconsistent evidence on how social media marketing (SMM) affects purchase intention for high-involvement products motivates this study of Instagram-based SMM among Generation Z and Millennial consumers of local Indonesian skincare brands. Grounded in the Theory of Planned Behavior, the study tests whether consumer involvement and attitude towards influencer-endorsed products mediate the SMM-purchase intention relationship. Data from 251 respondents were analyzed using PLS-SEM. All five hypotheses were supported: SMM most strongly drives involvement, which shapes attitude and directly raises purchase intention, while attitude towards influencer-endorsed products is the strongest predictor of purchase intention, and involvement significantly mediates the SMM-purchase intention link. The novelty lies in treating involvement as a full mediator rather than a moderator. Managerially, local skincare brands should build engaging, personalized Instagram content to raise involvement, then leverage credible influencers to shape attitude. SMM exposure alone does not directly drive purchase intention; it works through involvement and attitude formation